GRAVITY SURVEYS IN THE NORTH SUMATRA FOREARC - J. Milsom; Sarjono Dipowirjo; Baizar Sain; J. Sipahutar (Scientific Contributions Oil and Gas, 1990)
Land gravity surveys on the islands of the North Sumatra Forearc have defined regions of high fields and strong gradients, the majority of which seem to be associated with the presence of mafic and ultramafic rocks. The onshore data, obtained in the course of joint LEMIGAS-University of London expeditions, complements marine data obtained by American oceanographic institutes and allows gravity maps to be completed of the whole forearc regine.